Enabling sexual self-fashioning: embracing, rejecting and transgressing modernity among the Iranian Dutch. Issue 11 (18th August 2019) - Roodsaz, Rahil; Jansen, Willy
ABSTRACT: Modernity figures prominently in understanding change in diasporic sexual cultures, particularly when it comes to Muslim immigrants living in Western countries. Prevailing academic analyses of sexuality in the Iranian diaspora focus on the willingness and ability to embrace 'modern' notions of sexual liberty, individual self-fulfilment and gender equality. This approach attributes an assumed progression from a traditional past to a modern present to the Iranian immigrants, and determines simultaneously the extent of their integration into the 'host' culture. As an alternative to this dominant perception of change in which modernity is seen as an indicator of cultural progression, this paper proposes the concept of sexual self-fashioning to investigate the diasporic articulations of sexuality in various discursive uses of modernity as investments in processes of subjectivity. Based on an ethnographic research conducted between 2010 and 2014, the Iranian Dutch' perceptions of specific sexual issues are analysed as vehicles to sexual self-fashioning. It is argued that a sexual self is actively negotiated and created through embracing, rejecting and transgressing modernity, which enables the interlocutors to position themselves in different fields of socio-cultural or religious belonging.